The Influence of Personalized Web-Based Learning on The Mastery and Application of Concepts in Students with Different Learning Styles - Abdul Haris Indrakusuma; Setyosari, Punaji; Sulton; Waras (JTP - Jurnal Teknologi Pendidikan, 2024)
Conventional learning has limitations, leading researchers to propose personalized web-based learning tailored to individual student characteristics. This study focuses on enhancing web-based learning at Bhinneka PGRI University in Indonesia by customizing content and activities to align with students' learning styles. The research methodology uses a quasi-experimental design involving 72 information technology education students. Data collection includes assessments of learning styles, concept mastery, and concept application through tests. Descriptive statistical analysis shows that personalized web-based learning has a more positive influence on the mastery and application of concepts compared to non-personalized learning. There is no significant correlation between personalized web-based learning and students' learning styles. The findings indicate differences in mastery and application of concepts among students using web-based learning, but no disparities based on different learning styles. In conclusion, personalized web-based learning leads to variations in mastery and application of concepts compared to non-personalized methods, with no discernible discrepancy in the mastery and application of concepts between students with different learning styles. Research indicates that personalized web-based learning is more effective in enhancing mastery and application of concepts compared to non-personalized methods. By customizing web-based learning to individual learning styles, students can enhance the quality and outcomes of their learning.